Functionalization of E-Court System in Eradicating Judicial Corruption at The Level of Administrative Management - Muhamad Iqbal Iqbal; Susanto Susanto; Moh Sutoro (Jurnal Dinamika Hukum, 2019)
This study aims to determine the effectiveness of the implementation of E-Court to eradicate the activities of judicial corruption. Corruption in the administration sector is closely related to the relationship between justice seekers and court administration staff. The problems raised in this study are how functionalization of E-Court in eradicating judicial corruption in administrative management of cases in the courts in JABODETABEK and how to reform the management of administrative court in the future. This study uses an empirical method approach with descriptive analytical research specifications. This is because this research seeks to illustrate the facts of the effectiveness of the e-court system in eradicating corruption in the court administrative management sector. This concept of public service must be well understood by the judiciary. The functionalization of e-court is considered not optimal since many justice seekers do not know the existence and usefulness of the system. It is expected that the e-court system will support the establishment of the principle of quick, simple and low cost justice in the administrative management of cases. Keywords: E-Court, Court Administrative System, Corruption